A single amino acid determines the catalytic efficiency of two alkenal double bond reductases produced by the liverwort Plagiochasma appendiculatum. Issue 18 (13th August 2013) - Wu, Yifeng; Cai, Yuanheng; Sun, Yi; Xu, Ruixue; Yu, Haina; Han, Xiaojuan; Lou, Hongxiang; Cheng, Aixia
Abstract : Alkenal double bond reductases (DBRs) catalyze the NADPH‐dependent reduction of the α, β‐unsaturated double bond of many secondary metabolites. Two alkenal double bond reductase genes PaDBR1 and PaDBR2 were isolated from the liverwort species Plagiochasma appendiculatum . Recombinant PaDBR2 protein had a higher catalytic activity than PaDBR1 with respect to the reduction of the double bond present in hydroxycinnamyl aldehydes. The residue at position 56 appeared to be responsible for this difference in enzyme activity. The functionality of a C56 to Y56 mutation in PaDBR1 was similar to that of PaDBR2. Further site‐directed mutagenesis and structural modeling suggested that the phenol ring stacking between this residue and the substrate was an important determinant of catalytic efficiency. Abstract : Isolation of two double bond reductase (DBR) genes from liverworts. These two DBRs showed different substrate preference and catalytic efficiency. A single amino acid enhances the catalytic efficiency of DBR2 versus DBR1.